UPAYA MENGATASI KELEMAHAN MAHASISWA DALAM PERENCANAAN SISTEM LISTRIK INDUSTRI MELALUI PEMANFAATAN CAD (COMPUTER AIDED DESIGN) - Sukamta, Sri (Universitas Negeri Semarang, 2007)
The study has fur objectives. First, to know the effectiveness of the teaching byCAD method. Second, to assess the students’ ability in understanding the subject.Third, to know whether or not this new technique improves the students’ ability inunderstanding the topic being taught. Fourth, to know whether or not students enjoythis new technique. This research use two cycles. Each cycle consists of planning,action, observation, reflection, and evaluation. The data were collected with actiontests, in the form test of comprehension and analysis, questionnaire, interview, andobservation. Data analysis was done qualitatively and quantitatively. Quantitative datawas analyzed in percentage. The study concludes that: First; student spirit consistingthe indicators of motivation, time efficiency, material development, seriousness,responsibility, achievement spirit, team work, initiative, and participation tend to bebetter. Second, learning quality concerning learning management and classmanagement tends to be better. Third, students’ achievement including subjectunderstanding and analysis ability tends to be better. Fourth, the use of computer inthe subject of industrial electricity system planning is an effective learning variation toimprove students’ achievement.Kata kunci : upaya, kelemahan, perencanaan, CAD